2020
DOI: 10.1007/s00268-020-05570-7
|View full text |Cite
|
Sign up to set email alerts
|

Massage of the Hepatoduodenal Ligament Recovers Portal Vein Flow Immediately After the Pringle Maneuver in Hepatectomy

Abstract: Background The Pringle maneuver is often used in liver surgery to minimize bleeding during liver transection. Many authors have demonstrated that intermittent use of the Pringle maneuver is safe and effective when performed appropriately. However, some studies have reported that the Pringle maneuver is a significant risk factor for portal vein thrombosis. In this study, we evaluated the effectiveness of portal vein flow after the Pringle maneuver and the impact that massaging the hepatoduodenal ligament after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Recently, an interesting study was reported that massage of hepatoduodenal ligament recovers portal vein flow immediately after the Pringle maneuver in hepatectomy. 16 In the future, we plan to study the improvement of the Pringle maneuver technique to prevent postoperative PVT.…”
Section: Classification and Gradingmentioning
confidence: 99%
“…Recently, an interesting study was reported that massage of hepatoduodenal ligament recovers portal vein flow immediately after the Pringle maneuver in hepatectomy. 16 In the future, we plan to study the improvement of the Pringle maneuver technique to prevent postoperative PVT.…”
Section: Classification and Gradingmentioning
confidence: 99%